2001
DOI: 10.1021/ja015999k
|View full text |Cite
|
Sign up to set email alerts
|

2H MAS NMR Studies of the Manganese Dioxide Tunnel Structures and Hydroxides Used as Cathode Materials in Primary Batteries

Abstract: Variable-temperature (2)H MAS NMR spectroscopy was used to investigate the local environments and mobility of deuterons in the manganese dioxide tunnel structures. Five systems were investigated: electrolytic manganese dioxide (EMD), the model compounds groutite and manganite, and deuterium intercalated ramsdellite and pyrolusite. Ruetschi deuterons, located in the cation vacancy sites in EMD, were detected by NMR and give rise to a resonance at 150 ppm at room temperature. These deuterons are rigid on the (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 44 publications
3
54
0
Order By: Relevance
“…The Mn atoms have an antiferromagnetic interaction with magnetic moments of ±4 μB. [33,34] All relaxations of the lattice parameters and atomic positions were performed until residual forces were reduced to 0.01eV/Å. In a previous study [34], we found that incorporating van der Waals (vdW) forces using the DFT-D2 approach of Grimme, [35] applied to the α-MnO2 structure accommodating K + and H2O, produced a binding energy very similar to that of the DFT calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The Mn atoms have an antiferromagnetic interaction with magnetic moments of ±4 μB. [33,34] All relaxations of the lattice parameters and atomic positions were performed until residual forces were reduced to 0.01eV/Å. In a previous study [34], we found that incorporating van der Waals (vdW) forces using the DFT-D2 approach of Grimme, [35] applied to the α-MnO2 structure accommodating K + and H2O, produced a binding energy very similar to that of the DFT calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The calculation results obtained by applying Equation (5) tothe test data are presented in Figure 6, and their linear fitting analysis resultsare listed in Table 2. The S-shaped α = f (t) curves are commonly analyzed by the Hancock and Sharp's method [26,27]:…”
Section: Determination Of the Kinetic Modelmentioning
confidence: 99%
“…As shown in Figure 4, the incubation period shortened and the reaction rate increased with the increase of the roasting temperature. The S-shaped α = f(t) curves are commonly analyzed by the Hancock and Sharp's method [26,27]:…”
Section: Determination Of the Kinetic Modelmentioning
confidence: 99%
“…In addition, high deposition rate of ␥-MnO 2 may lead to an increasing trend of H 2 O inclusion into the lattice. EMD generally contains ∼4 wt.% of structural water in the lattice, which dramatically influences not only electrochemical properties but also other properties such as the density and the electronic conductivity [29].…”
Section: Possible Relations Between Pcd Parameters With Deposition Kimentioning
confidence: 99%